History and influence of ancient music - Wilson, Olive Mabelle (My University, 1895)
Introduction: The history of music is a very interesting one, especially the music of the ancients. Unlike architecture, sculpture, and painting, music is necessarily ephemeral in its material form and so we possess no specimens to inform us of its character during remote periods, but we know that it has been cultivated even among the most uncivilized races of men, from time immemorial. It’s existence may be traced through all the Greek philosophies and mythologies. We have the myth of the sirens, who lured the ill-fated mariners to destruction by their sweet song. We also have a trace of it on the Egyptian obelisks and ancient tombs “everywhere gilding the twilight of antiquity with its suggestive presence.” It is strand and still not strange that in all countries, ancient and modern, music has been used as a part of all religious rites and ceremonies, it is the highest praise that can be given to the gods and the Creator, it seems to be the connecting link and the divine link between the people and their Gods. There are many myths in regard to the origin of music. The Greeks had a mathematical and astronomical theory which was probably taken from the Egyptians. They believed that the scale was founded on the seven planets known to astronomers at that time. Moon, Mercury, Venus, Sun, Mars, Jupiter, and Saturn. The sun was supposed to be the controlling middle note around which all the others circled.
Citation: Wilson, Olive Mabelle. History and influence of ancient music. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Music; Ancient music; History of music; Theses; Manuscripts (documents)